Orchid Pollination: An Observation on Pollination-Pollinator Interaction in Cymbidium pendulum (Sw.) Roxb. - and Ravi Kant, Lucky K. Attri* (Current Botany, 2011)
The path of pollination in Cymbidium pendulum (Sw.) Roxb. has been traced in the present studies. The honey been identified as Apis mellifera was found to act as main pollinator and this bee is the only insects, among others, who succeeded in performing pollination because probably due to its structural compatibility with the plant species. Pollination by Apis mellifera bees was suggested to occur in a number of families but rare phenomenon in orchids and it is first time that the species was observed to pollinate the Cymbidium pendulum flowers. Bee moved around the flowers for some times, entered the flower and carried on pollinia along with on the back during its journey. It revisited the different flower and deposited its pollinia on to it and the act of pollination was accomplished. SEM study showed an intricate network on the back of bee thus clearly indicates its role in firm attachment to pollinia.Ã‚Â 